Application of Deterministic Simulation Modeling for Capital Structure Robustness Testing: A Case Study in the Capital-Intensive Industry (AGII) - Legiman Samosir; Haikal Habibi Siregar (CV. Multimedia Teknologi Kreatif, 2026)
In the capital-intensive sector, the strategic management of capital structure is often constrained by cost rigidity, where high fixed costs magnify the impact of demand volatility on corporate solvency. This study addresses the methodological gap in static financial analysis by applying Deterministic Simulation Modeling to conduct a Robustness Test on PT Aneka Gas Industri Tbk (AGII). The primary objective is to measure the structural resilience of the firm against operational shocks specifically demand fluctuations attributed to the bullwhip effect and to evaluate the efficacy of refinancing as a risk mitigation strategy. Using audited financial data, the simulation executes specific